PENINGKATAN KEMAMPUAN MENULIS MELALUI PELATIHAN KARTU AKTIF SISWA SMPN SATU ATAP PULAU KOMODO KABUPATEN MANGGARAI BARAT - Parama Santati; Eogenie Lakilaki (Universitas Mataram, 2023)
Improving the quality of education in Indonesia should be carried out intensively, especially in the 3T (Frontier, Remote, and Disadvantaged) regions. One effort that can be done is Community Service activities, such as KARTU AKTIF Training (Scientific Writing and Interactive Activities). This activity was motivated by the PISA survey which stated the low reading ability index in Indonesia. Programs to improve writing skills are urgent nowadays, because according to research, there is a relationship between reading interest and writing ability. So that the students of the Komodo Island Satu Atap Junior High School can have writing and observation skills, as well as trigger a superior character, namely social awareness. In addition, students are also expected to be more accomplished in the field of writing. The number of target audiences is 57 students of Satu Atap Junior Hight School on Komodo Island, West Manggarai Regency. The steps taken include identifying problems, collecting data and information, designing materials, providing training, and carrying out evaluations. Training activities are carried out in the form of lectures in the form of delivering material on writing Observation Results Reports, then interactive activities in the form of question and answer sessions and observing certain objects accompanied by tutors, and ending with compiling Observation Reports. The training activity was carried out for two days. The first day was the presentation of material on the Observation Results Report based on the 2013 Curriculum Indonesian language material, observing objects, and preparing Observation Results Reports. On the second day, the Education Division conducted an assessment and appreciated the Observation Reports prepared by the students. After attending the training, 57.89% of the participants had an average score of 71.75 or the